miR-22 has a potent anti-tumour role with therapeutic potential in acute myeloid leukaemia - Xi Jiang (Nature Portfolio, 2016)
Mir-22 has been shown to be an oncogenic microRNA in breast cancer and myelodysplastic syndrome. Here, the authors show that mir-22 functions as a tumour suppressor in de novoacute myeloid leukaemia by inhibiting the expression of several oncogenes and that restoring mir-22 expression suppresses AML progression.